Isolation and molecular identification of Fusobacterium nucleatum from Nigerian patients with oro-facial infections. - Nwaokori, Francisca Obiageri; Coker, Akitoye; Ogunsola, Folasade; Campos, Mário Júlio Ávila; Patricia, Ayanbadejo; Umeizudike, K. A.; Abdurraq, O. T.; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2011)
Fusobacterium nucleatum is one of the most common anaerobic bacteria present in the oral cavity and is often isolated from infections involving other body sites. To characterise F. nucleatum strains from patients attending a teaching hospital in Nigeria in order to provide information on the methods for accurate identification of anaerobes in clinical specimen. Fusobacterium nucleatum specie from 50 patients presenting with oro-facial infections were studied by culture on Fusobacterium selective agar and fastidious anaerobe agar. The isolates were characterised based on colonial morphology, microscopy, lipase production, susceptibility to kanamycin and colistin and resistance to vancomycin. Biochemical tests were performed using a commercial test kit. The identity of the isolates was confirmed based on molecular characterization performed using polymerase chain reaction (PCR) analysis. Forty-eight (96%) F. nucleatum isolates were obtained from the 50 patients by culture and all the isolates were identified by colonial appearance and microscopy based on their unique spindle shape with tapered ends. Only 26 (54.2%) of the 48 isolates were identified by commercial API 20A test kit while PCR confirmed the identity of all the isolates. Anaerobes are involved in human infections and their study is quite cumbersome due to tedious nature and high cost of the techniques involved. Cultural method is reliable in the isolation and identification of F. nucleatum species. PCR is a rapid and simple method that can complement the phenotypic identification of anaerobes and would assist in their full identification.